Improving Teacher's Performance through Change Leadership: Mediated by Job Satisfaction - Firmansyah, Fahmie; Sudadio, Sudadio; Juansah, Dase Erwin (Graduate Program Magister Manajemen Pendidikan, 2025)
The purpose of this study is to see the effect of change leadership on teacher’s performance through job satisfaction on the performance of Junior High School (SMP) teachers in Cilegon City. The method was ex post facto and uses a questionnaire and research data analysis using path analysis to understand the causal relationship between variables in a model. The results of the study indicate that change leadership has an indirect effect on teacher’s performance through job satisfaction. The results of this study present novelty by exploring the role of job satisfaction as a mediator in the relationship between change leadership and teacher’s performance. The findings of this study offer new insights into the importance of job satisfaction in strengthening the positive effects of change leadership on teacher’s performance.